Winning the international market: unveiling the art of product selection via local e-commerce platform - Lai, Kah Shen (2024)
In the competitive global e-commerce landscape today, this study examines the key factors influencing product selection decisions among Malaysian e-commerce sellers. Drawing upon the Unified Theory of Acceptance and Use of Technology (UTAUT) model, the research aims to investigates the impact of logistic performance expectancy, virtual community building, effort expectancy, and trialability on product and platform familiarity. A quantitative approach with a sample of 316 e-commerce sellers was used, utilizing a survey-based methodology. The findings, as examined through Structural Equation Modeling (SEM), demonstrated strong positive relationships between the identified factors and product and platform familiarity. On the other hand, increased familiarity was found to significantly impact product selection decisions. These findings underscore the important role of these factors in enhancing seller decision-making processes within the e-commerce landscape. However, limitations such as the geographical scope and reliance on quantitative data suggest the need for future research to incorporate diverse samples and qualitative methodologies to improve the generalizability and depth of the findings. The study contributed valuable insights for e-commerce sellers and platform developers looking to optimize product selection strategies, improve competitiveness, and navigate the dynamic e-commerce market effectively.